Musculoskeletal symptoms in nurses at a primary care hospital in Pachuca, Hidalgo. Mexico - Josefina Reynoso Vázquez,; Leonardo Daniel Trujillo Mancera,; Arturo Salazar Campos,; Sonia Maetzin León Alvarado,; Olga Rocío Flores Chávez,; María del Carmen López Zermeño,; David Pérez Becker,; Jesús Carlos Ruvalcaba Ledezma, (Public Health, 2026)
Musculoskeletal disorders represent a major problem in developing countries as they generate high economic costs and are recognized as a considerable cause of absenteeism and disability. The objective of this research was to describe the main risk factors associated with musculoskeletal disorders affecting nursing staff working at a Primary Care Hospital in Pachuca, Hidalgo, Mexico. Methodology. A quantitative study was conducted with a cross-sectional, observational design. Forty-nine nurses from the trauma service participated. Results. The most common gender was female (83.7%), while eight male nurses participated (16.3%). The mean age was 37 years, with a range of 25 to 53 years. Pain was observed to be the most common musculoskeletal symptom (87.5%). Similarly, the regions most affected by musculoskeletal injuries were the lower back (74.8%), followed by the neck (72.3%), and the upper back (64%). Conclusion. There is a high prevalence of MSDs in nursing staff, with pain being the most common symptom and with varying frequencies in relation to the affected region, the main ones being the lower back, neck and upper back.